A survey of experience-based preference of Nickel-Titanium rotary files and incidence of fracture among general dentists - WooCheol Lee; Minju Song; Euiseong Kim; Hyojin Lee; Hyeon-Cheol Kim (Korean Academy of Conservative Dentistry, 2012)
Objectives The purpose was to investigate the preference and usage technique of NiTi rotary instruments and to retrieve data on the frequency of re-use and the estimated incidence of file separation in the clinical practice among general dentists. Materials and Methods A survey was disseminated via e-mail and on-site to 673 general dentists. The correlation between the operator's experience or preferred technique and frequency of re-use or incidence of file fracture was assessed. Results A total of 348 dentists (51.7%) responded. The most frequently used NiTi instruments was ProFile (39.8%) followed by ProTaper. The most preferred preparation technique was crown-down (44.6%). 54.3% of the respondents re-used NiTi files more than 10 times. There was a significant correlation between experience with NiTi files and the number of reuses (p = 0.0025). 54.6% of the respondents estimated experiencing file separation less than 5 times per year. The frequency of separation was significantly correlated with the instrumentation technique (p = 0.0003). Conclusions A large number of general dentists in Korea prefer to re-use NiTi rotary files. As their experience with NiTi files increased, the number of re-uses increased, while the frequency of breakage decreased. Operators who adopt the hybrid technique showed less tendency of separation even with the increased number of re-use.